Work Coffee Indonesia Marketing Communication Strategy Through a Zero Percent Plastic Campaign In Increase Brand Figure - Surya Eka Desayu; Astiani Ririn (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The research purpose is to find out the communication strategy used by Work Coffee Indonesia in improving its brand Figure as the coffee shop business is growing rapidly and competing fiercely. The research is conducted with a qualitative approach, descriptive method. The data collection technique is through literatu e study and field study, observation, interviews, and documentation, while the research informants are obtained through purposive sampling technique. The rescarch results indicate that Work Coffee Indonesia is running a Zero Percent Plastic Campaign by carrying out several activities called Waste Management, namely Positive Green Energy and Against Single-Use Plastic by sorting waste with the goal that Work Coffee Indonesia is to become a friendly environment coffee shop. Furthermore, to show good examples for customers and other coffee shops' awareness in environmental care programs. The messages conveyed are information and persuasion messages both verbally and non- verbally, namely a series of messages that can change new habits in consumers, while the zero percent plastic campaign through the social media of Instagram and the Website. Conclusion The research shows that the communication strategy implemented to increase the brand Figure has achieved the goals conceptualized by Works Coffee Indonesia Bandung, although for promotional achievements it still needs development in the use of information media. Research Suggestions is that Work Coffee should hold events or seminars more often to educate about programs or campaigns held by them for their very positive program. In addition, social media development such as TikTok and YouTube to share videos with creative content to reach a wider audience is needed.